The Effectiveness of Vitamin C Supplementation and Ambon Banana on Hemoglobin Levels in Anemia Young Women - Dewi Pertiwi Dyah Kusudaryati; Ratih Prananingrum (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Iron deficiency anemia is an anemia due to iron deficiency which results in impaired hemoglobin synthesis. Young women are prone to anemia due to menstruation every month. Efforts to increase hemoglobin levels can be done by supplementing vitamin C and giving foods that are high in iron such as Ambon banana. The aim of this research is to determine the effectiveness of vitamin C supplementation and Ambon banana on hemoglobin levels in anemia young women. Pretest posttest two groups design with 18 subjects each group. Subjects were anemic young women. Group I was given vitamin C supplemen and Ambon banana while group II was given Ambon banana. Treatment is given twice a day for 8 days. Hemoglobin level data was taken by taking blood at the fingertips. In group I there were differences in hemoglobin levels before and after vitamin C supplementation and Ambon banana (p = 0,000). In group II there were also differences in hemoglobin levels before and after administration of Ambon banana (p = 0.001). Group I had an increase in average hemoglobin level of 1.5 ± 1.0 g /dl while group II had an increase in average hemoglobin level of 1.2 ± 1.2 g/dl. The conclusion is Vitamin C supplementation and Ambon banana are effectively increased hemoglobin levels in anemic young women.